Potential loss of prognostic significance of minimal residual disease assessment after R‐CHOP‐based induction in elderly patients with mantle cell lymphoma in the era of rituximab maintenance. Issue 5 (13th September 2018) - Klener, Pavel; Fronkova, Eva; Kalinova, Marketa; Belada, David; Forsterova, Kristina; Pytlik, Robert; Blahovcova, Petra; Simkovic, Martin; Salek, David; Mocikova, Heidi; Prochazka, Vit; Janikova, Andrea; et al.
Abstract: Rituximab maintenance (RM) prolongs survival of elderly patients with mantle cell lymphoma (MCL). Persistent minimal residual disease (MRD) after induction repeatedly correlated with shorter progression‐free survival (PFS). However, none of the published studies analyzed patients treated with RM. The main purpose was to analyze prognostic significance of MRD in the elderly patients with newly diagnosed MCL treated according to the recently published observational trial protocol (alternation of R‐CHOP and R‐cytarabine, 3 + 3 cycles, GovTrial number NCT03054883) at the centers that implemented RM. Minimal residual disease was evaluated by a EuroMRD standardized real‐time PCR approach after 3 and 6 cycles of the induction therapy. Prognostic significance of MRD was analyzed in a subcohort of patients treated at the centers that implemented RM as a standard approach. Bone marrow proved to be a significantly more sensitive source for MRD detection than peripheral blood. In either compartment MRD (positive versus negative) after 3 or 6 cycles of the induction therapy did not correlate with PFS. The observed loss of prognostic significance of MRD after the R‐CHOP‐based induction appears to be a consequence of RM immune control over the residual lymphoma.